Kin Endogamy and the Blood Taint in Ancient Egypt and Nigeria (2019)
Kin Endogamy, marriage between siblings, has been a practice among several cultures of the world. This is a deviation from positions of sociologists, anthropologists and psychologists on a universal incest taboo even as they premised it on four theories; the demographic, indifference, repression and evolution theories. Several scholars have discussed kin endogamy in the pre-Christian and Christian eras of the Greco-Roman societies citing evidences; explaining that indication of close-kin marriage could have been adoption rather than incest; and noting that royal incest may have been occasioned by the quest for ultimate power, even in the Ptolemaic dynasty. This paper took an in-depth study of sibling marriage in Ptolemaic Egypt and in some communities in Nigeria, with a view to understanding the rationale behind this socio-cultural practice and its effects on inbred children. The paper argues that it is highly probable that this consanguineous marriage even among the Ptolemies of Egypt may have resulted in genetic/biological and psychological setbacks among inbred descendants such that assassinations among siblings for power became the order of the day. The study further argued that kin endogamy was practiced due to, among others, the ideology of the blood taint or pure blood. Further studies that may examine exogamous culture in the Greco-Roman world and Nigeria were recommended.